Methanolic Root Extract of Rauwolfia serpentina Lowers Atherogenic Dyslipidemia, Arteriosclerosis and Glycosylation Indices in Type 1 Diabetic Mice - Muhammad Bilal Azmi & , Shamim A Qureshi, Sumera Rais, Saleha Sultana (Journal of Applied Pharmaceutical Science, 2015)
Globally recognized antihypertensive phytomedicine Rauwolfia serpentina Benth is also well-known for its diversified ethno-medicinal usefulness. The objective of present study is to evaluate the effect of methanolic root extract (MREt) of R. serpentina on atherogenic dyslipidemia, arteriosclerosis and glycosylation indices in alloxan-induced type 1 diabetic mice. After the single intraperitoneal injection of alloxan monohydrate (150 mg/kg), forty two mice were allocated into diabetic control (1 ml distilled water), negative control (0.05% DMSO 1 ml/kg), positive control (5 mg/kg glibencalmide) and three test dose groups (MREt 10, 30 & 60 mg/kg). Normal control (1ml distilled water) was also used. After 14 days of respective treatments, fasting blood glucose, insulin, haemoglobin (Hb), glycosylated haemoglobin (HbA1c), triglyceride (TG), total cholesterol (T-CHOL), low density lipoprotein cholesterol (LDL-c), very low density lipoprotein cholesterol (VLDL-c), and high density lipoprotein cholesterol (HDL-c) levels were determined. Wet organ weight, relative weight, percent change in glycosylation and non-HDL-c level was also determined. MREt maintained the wet organ and relative weight, as did not produce any harmful changes in kidney, liver, spleen and heart. Significant reduction in percent glycosylation was observed from -37.35 to -48% in all test groups. Upto two fold significant (p< 0.0001) decrease in atherogenic (AI) and arteriosclerotic (ArtI) indices, while improvements in atherogenic dyslipidemia ratio (ADR) were also observed in all test groups. Significantly (p< 0.0001) lowered level of non-HDL-c and glucose to lipid profile ratios were estimated in all test groups. The obtained results indicated the therapeutic potential of MREt in lowering the risk of atherogenic dyslipidemia, arteriosclerosis and glycosylation in alloxan-induced diabetic mice.
Keywords: Atherogenic index, cholesterol, triglycerides, Rauwolfia serpentina.